2-Dimensional Materials for Performance Enhancement of Surface Plasmon Resonance Biosensor: Review Paper - Chandra Wulandari; Ni Luh Wulan Septiani; Nugraha Nugraha; Ahmad Nuruddin; Brian Yuliarto (Journal of Engineering and Technological Sciences, 2023)
Surface plasmon resonance (SPR)--based biosensors compete and excel among optical biosensors because of exceptional features such as high sensitivity, label-free, and real-time measurement, allowing the observation of molecular binding kinetics. In SPR biosensors and other biosensor techniques, surface functionalization and bioreceptor attachment are effective strategies to improve sensor performance. The application of an appropriate immobilization matrix for the bioreceptor is an essential step in maximizing the absorption of the bioreceptor on the sensor surface, thereby improving a specific target-sensor interaction. Furthermore, the materials should provide excellent optical properties to enhance the response signal. The high surface-to-volume ratio and high optical absorption of 2D materials qualify these requirements, thus promising advancements for SPR biosensors. This article reviews the recent SPR biosensor study with the use of the 2D materials family to improve the sensor performance, including graphene, transition metal dichalcogenides (TMDCs), MXene, black phosphorus (BP), perovskite, and boron nitride (BN). The materials properties and enhancement mechanisms of different 2D materials are discussed comprehensively. This review was expected to provide a future perspective and design approach for 2D materials-based SPR biosensors.